BBB Disease prevalence and shade tree diversity in smallholder cocoa (Theobroma cacao) farms: case of Bundibugyo District, Western Uganda: Disease prevalence and shade tree diversity in smallholder cocoa (Theobroma cacao) farms: case of Bundibugyo District, Western Uganda - Bwambale Bisereko, Blasio; Sseremba, Godfrey; Mwine, Julius (International Journal of Scientific Research and Management (IJSRM), 2021)
Cocoa (Theobroma cacao) growing systems in Uganda consists of shade systems with different tree species. Tree shade systems are the pure stand trees in the cocoa plantation which have been attributed towards reducing on pests and disease incidences, shade provision, boosting fertility, Agro biodiversity, fodder and improving production. The study was aimed at identifying potential shade tree species that can minimize disease threats on cocoa farms. Eighty-two cocoa farmers were reached out of 120 cocoa farmers in Bundibugyo that possessed at least five acres of the plantation in a purposive sampling approach.Black pod disease was non-significantly associated with presence of shade tree diversities. It was established that incidence of black pod rot disease was non-significantly associated with presence of all shade tree species; association between witch’s broom disease incidence with presence of Maesopsis eminii was highly significant (χ2= 55.41, (p